Impacts of Using Building Information Modelling (BIM) in Sustainable Green Building Projects - Gurgun, Asli Pelin; Koc, Kerim; Atabay, Senay (TURKISH CHAMBER CIVIL ENGINEERS, 2022)
Rapid consumption of natural resources and uncontrolled increasing population made sustainability necessary in the construction industry, as in many other areas. Building Information Modeling (BIM) applications have been used as an important tool in the construction industry in recent years to achieve this goal. In this study, the advantages of using BIM in sustainable green building projects were investigated in two main parts. In the first part, the advantages of using BIM in sustainable projects according to effective project phases were examined. In the second part, contributions of BIM to cost, duration, scope and quality constraints were analyzed. The results indicate that interdisciplinary collaborating environment has been identified as the most important advantage and these advantages could vary according to project phases.
Keywords: Building information modelling; sustainable buildings; project phases; project constraints; CONSTRUCTION PROJECTS; BENEFITS; ENERGY; Engineering